Management of Teaching Material Development Competency-Based to Increase Life Skill Vocational High School Students - Nurjaman, Ujang; Sujiarto, Heru; Khoeriyah, N. Dede; Khori, Ahmad (Journal of Architectural Research and Education, 2021)
This study aims to  determine the  competency-based  teaching materials development program to improve student life skills, implementation, problems and challenges, and future improvement steps. The method used in this research is descriptive qualitative. This research was conducted at the Ma'arif Nahdotul Ulama Vocational High School, Garut Regency, West Java Province. The data collection techniques were interviews and documentation, while the data analysis techniques used were qualitative data analysis techniques using an inductive approach. The research results are: First, the teaching material development program carried out is planning  development  quality  objectives,  establishing  a  School  Activity Plan, collaborating with the business world and the industrial world. Second, the  implementation  is  that  the  partnership  relationship  is  not  optimal. Implementing the guidelines for the development of teaching materials is not optimal. Good management is needed in implementing the results of the development of teaching materials, and an additional budget is required. Third, the problems faced are poor management of school principals, inadequate curriculum development and cooperation,  preliminary school budgets, a productive syllabus that needs to be developed, and industrial practices for production are not optimal. Simultaneously, the future challenges are the student resources managing the partnership, the students' character, and  the demands for  practical facilities that require special attention.  Fourth, the  corrective  steps  are that the regulation of material development needs particular attention, additional budget is needed, the apprenticeship material must adjust to the productive syllabus, quality learning, improved competency tests, the competence of educators needs to be improved, optimizing the acceptance of new students, completing facilities and infrastructure.